How to Measure Complex Problem Solving Skills: A Systematic Literature Review - Eko Juliyanto; Wiyanto Wiyanto; Sunyoto Eko Nugroho; Budi Naini Mindyarto (Universitas Negeri Semarang, 2021)
The purpose of this study is to conduct a literature review on measuring the Complex Problem Solving (CPS) skills. This study examines the instruments used to measure the CPS skills in the past 10-15 years. In addition, this study also describes indicators for measuring CPS skills. This type of research used in this study is a systematic literature review study using the PRISMA principle. The results showed that most of the CPS measurement instruments used in the journal articles reviewed were computer-based tests. Computer-based tests were chosen because they can simulate a dynamic environment. The CPS studies reviewed did not use certain CPS indicators and became a standard. The CPS indicators used are adjusted to the research theme being carried out.